Strategies of Indigenous Knowledge Management in Libraries - Sarkhel, Juran Krishna (Qualitative and Quantitative Methods in Libraries; Vol 5 No 2 (2016): June 2016 Issue, 2017)
Indigenous knowledge (IK) is the knowledge that people in a given community developed over time, and has made positive contributions towards sustainable development. Indigenous communities around the world face ongoing threats to the survival of their indigenous knowledge in view of its tacit nature. Traditionally, libraries have concentrated more on promoting a reading culture than on managing and promoting IK. If IK is well documented, packaged and deposited in libraries and information centres, it could be directly accessed by individuals.The study explores how the indigenous knowledge can best be managed in the libraries in order to contribute positively to the community. Within this area of interest, this paper answers the question: what roles the library professionals can play in the management and preservation of IK. While highlighting the IFLA mandate towards the management and preservation of IK, different activities associated with the management of IK — such as, collection, recording and documentation, organization, preservation and storage, dissemination and networking are discussed. Concludes that library professionals need to be proactive in devising strategies for the management and preservation of IK with the help of their professional knowledge and skills in order to ensure access to this valuable resource.